Cultural Arts Teachers' Creative Strategies In Enhancing Students' Creativity And Motivation Through Ensemble Music Learning - Widyaswara, Silvana Nada; Suharto, Suharto; Lestari, Wahyu (Universitas Negeri Surabaya, 2024)
This study explores the role of creativity of art and culture teachers in teaching music ensembles at SMP Regina Pacis Surakarta. Creativity is an important element in developing students' musical skills and values, such as cooperation, discipline, and appreciation for cultural arts. Using a qualitative approach with an exploratory research design, this study reveals the strategies and methods used by teachers to guide students in creating unique and high-quality music ensembles. The results show that the teacher, Mr. Nugroho Purna Widiyanto, S.Pd., implements creative teaching methods such as demonstration, practice, and peer tutoring, as well as creatively arranging traditional songs to enhance students' interest and understanding of music. This research emphasizes the importance of a creative approach in teaching music to motivate and inspire students, as well as help them develop strong musical abilities and character.